Ethnopharmacological studies of Cecropia obtusifolia (Urticaceae) and its importance in the treatment of type 2 diabetes mellitus: A mini-review - Cadena-Zamudio, Jorge David; Nicasio-Torres, María del Pilar; Guerrero-Analco, José Antonio; Ibarra-Laclette, Enrique (Instituto de Ecología, A.C., 2018)
Background and Aims: Diabetes mellitus type 2 (DM-2) is one of the most recurrent chronic diseases worldwide, it is usually treated with synthetic medications, many of which have important repercussions on the patient's body. For this reason, ethnopharmacology has become more important in recent years, because a large number of plant resources origin are used in medicine and are shown as positive effect in the treatment of different diseases, including DM-2. Therefore, the aim of this review is to highlight how previous studies are adding to the understanding and knowledge of the biological effects reported in Cecropia obtusifolia, a tropical plant included in the Herbal Pharmacopoeia of the United Mexican States (FHEUM), which is commonly used to treat DM-2.Methods: A profound literature review was carried out on C. obtusifolia, focusing on diverse phytochemical, pharmacological, clinical and toxicological studies, as well as on some other relevant research findings.Key results: It is recognized that this species is able to decrease serum glucose, cholesterol and triglyceride levels due to its hypoglycemic and hypolipidemic properties, which has been demonstrated both in animal and human experimental models, attributing these effects to chlorogenic acid and isoorientin. These previous reports suggest that C. obtusifolia is a promising candidate for the development of a phytopharmaceutical which could be used in the treatment of DM-2.Conclusions: We provide an updated and complete overview of the phytochemistry, traditional uses, and pharmacological activities of C. obtusifolia. Regarding its pharmacological activities, we focus mainly on the hypoglycemic effect of this plant which supports its traditional use in DM-2 control. Moreover, the present knowledge was critically assessed to provide some evidence and justifications and propose future research prospects.